SEAPOP studies in the Lofoten and Barents Sea area in 2006 - Anker-Nilssen, Tycho; Barrett, Robert T.; Bustnes, Jan Ove; Erikstad, Kjell Einar; Fauchald, Per; Lorentsen, Svein-Håkon; Steen, Harald; Strøm, Hallvard; Systad, Geir Helge; Tveraa, T (Norsk institutt for naturforskning, 2007)
This is the second annual report of the SEAPOP programme, which was initiated in 2005. In 2006, the programme was extended to the near full scale in the Lofoten-Barents Sea area, but it is aimed for implementation at the national level within few years. The report is divided into three sections. The first is an executive summary, the second presents five selected highlights from the studies in 2006, whereas the third presents results from other projects within the programme. The programme is wide-ranging, and with about 20 activities running in parallel, there is no room for emphasising details of the results in this short abstract. The main effort is however being put into mapping and monitoring. The most demanding activity is to build-up the long-term data series for the numerical development, reproduction, survival and diet of an ecological and geographical selection of breeding populations. These data series are compared and analysed in relation to various environmental factors in an attempt to find the cause of the documented changes and to predict future population trends. This work is made at a series of key-sites spread from north to south: Spitsbergen, Bjørnøya, Hornøya, Hjelmsøya, Grindøya, Anda and Røst. More keysites will be established further south when the programme is extended to the national scale. Seabirds are mapped both along the coast and at sea. To balance resource use against minimum requirements for validity of data, coastal areas are covered such that each area is mapped once every ten years in each season (breeding, moulting/autumn, winter and spring periods). A habitat model predicting the distribution of coastal seabirds has also been developed. For seabirds at sea, the focus is put on modelling distributions in different seasons from documented associations between seabird occurrences, oceanographic factors and distributions of prey. These associations are derived from data collected in a multi-disciplinary cooperation within the ecosystem surveys of the Institute of Marine Research. ...